The Influence of Civil Servants' Perceptions on Position Transfer Policies on Work Objectives in the Buleleng Regency Government - Made Anik Widyastuti; Putu Indah Rahmawati; Ni Made Ary Widiastini (Budapest International Research and Critics University, 2022)
This study aims to analyze the implementation of the policy of shifting structural to functional positions and to compare employee job satisfaction in structural and functional positions in the Buleleng Regency Government. The total population in this study were 308 echelon III and IV employees who were affected by the transfer of positions and the number of samples was 174 employees who were determined by purposive sampling technique. Data analysis used a mixed method approach through qualitative descriptive analysis and quantitative analysis. The results showed that the implementation of the policy of shifting positions from structural to functional in the Buleleng Regency Government was one of the changes in the organization that occurred because of the rules/policies from the center with the aim of improving public services. This transfer of position will change the organizational structure and affect the career, mindset and job satisfaction of Civil Servants (PNS) but the implementation of this transfer is still not optimal because there are still obstacles faced, such as the process and procedures for assessing credit scores for promotions that do not exist. clarity. Based on the results of quantitative analysis with descriptive statistics that the perception of civil servants is higher in structural positions than in functional positions because civil servants feel a high level of job satisfaction while still occupying structural positions compared to after being transferred to functional positions. There is a significant difference in the job satisfaction of civil servants before the transfer of positions (structural) and job satisfaction of civil servants after the transfer of positions (functional). Job satisfaction in structural positions is greater than after being transferred to functional positions with dominant indicators shown by promotion, competence and income/salary.